PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PENILAIAN KINERJA MANAJERIAL PUSAT BIAYA PADA DINAS KELUARGA BERENCANA, PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN TULUNGAGUNG - Nadila Hananingrum; Dyah Pravitasari (UIN Sunan Gunung Djati Bandung, 2022)
In Indonesia, there are several instances of budget anomalies in the national and municipal levels of government. As a result, there is a waste of funds. Furthermore, the community wants the government to use state funds more wisely so that it can be more effective, efficient, transparent, accountable, and responsible. The purpose of this research was to see how the Department of Family Planning, Women's Empowerment, and Child Protection, Tulungagung Regency worked, used accountability accounting as a tool for evaluating the managerial performance of cost centers; to identify obstacles to implementing accountability accounting; and to solve issues to that arise during the adoption of accountability accounting. In this study used descriptive qualitative method as a research method. Observation techniques, interviews, and documentation were used to obtain data. According to the findings of the study, responsibility accounting has been adequately implemented and meets the requirements and characteristics of responsibility accounting. Keyword: performance assessment, responsibility accounting, cost center, budget, program realization